Defining the proxy design pattern using UML profile - Garis, Ana Gabriela (2006)
Today software solutions are often modeled using UML. Design patterns are frequently instantiated within these particular solutions. However, in several situations, UML is not expressive enough to describe them properly. UML profiles extend UML syntax and semantic in order to model elements of particular domains. As profiles extend UML vocabulary; design patterns define a common vocabulary for software designers. Because of this, it is possible to use a profile to define a design pattern’s vocabulary in UML. Profiles can be used to solve particular problems in different domains. This work shows a way in which profiles can be used to define design patterns. The definition of the proxy design pattern is shown as an example of our proposal.